2016
DOI: 10.1002/eat.22642
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of three universal eating disorder risk reduction programs by participants with higher and lower baseline shape and weight concern

Abstract: This study highlights the need for moderator analyses to become more routinely conducted in universal trials, to ensure that participants across baseline risk levels are benefiting and not harmed from program participation. © 2016 Wiley Periodicals, Inc. (Int J Eat Disord 2017; 50:66-75).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…A specific challenge to navigate is the integration of obesity prevention, which can encourage dietary restriction, and eating disorder prevention, which discourages the use of rigid practices of restriction. While these approaches do not necessarily lead to incompatible outcomes (Austin, Field, Wiecha, Peterson, & Gortmaker, ; Austin et al ., ), a focus on healthy eating has been shown to lead to an increase in eating concern and skipping more meals over 12‐month follow‐up in adolescents with higher baseline levels of shape and weight concern (Wilksch et al ., ). Given the potential for long‐term harm that can be caused by such behaviours, more work is required to understand how to safely present prevention messages related to nutrition and health in adolescents, especially those who are already showing vulnerability to DE.…”
Section: Discussionmentioning
confidence: 97%
“…A specific challenge to navigate is the integration of obesity prevention, which can encourage dietary restriction, and eating disorder prevention, which discourages the use of rigid practices of restriction. While these approaches do not necessarily lead to incompatible outcomes (Austin, Field, Wiecha, Peterson, & Gortmaker, ; Austin et al ., ), a focus on healthy eating has been shown to lead to an increase in eating concern and skipping more meals over 12‐month follow‐up in adolescents with higher baseline levels of shape and weight concern (Wilksch et al ., ). Given the potential for long‐term harm that can be caused by such behaviours, more work is required to understand how to safely present prevention messages related to nutrition and health in adolescents, especially those who are already showing vulnerability to DE.…”
Section: Discussionmentioning
confidence: 97%
“…However, scalability of such programmes is limited, and acceptability, feasibility, and efficacy are varied [93]. Among the interventions, media literacy, when universally delivered, has been found to be an effective intervention for improving ED symptoms, encouraging behaviour change, and reducing risk factors in the long-term leading to sustainable changes in adolescent health [97][98][99][100]. While media literacy prevention interventions have been proven effective in improving ED symptoms, further exploration is needed in the context of the new media environment to re-evaluate and refine these interventions to maximise their effects [167].…”
Section: Discussionmentioning
confidence: 99%
“…Of the three interventions, Media Smart was the only program where both ED and obesity risk factors were reduced among participants [97]. Further analysis of study outcomes found that, among participants with higher shape/weight concern at baseline, participation in Life Smart and HELPP increased eating concern and led to higher rates of meal skipping compared to controls [98].…”
Section: Universal Multi-risk Factor Programsmentioning
confidence: 97%
See 1 more Smart Citation
“…Owing to several layers of dependency in the outcome data, linear mixed regression models were fit, as suggested in comparable studies. 33 Students were nested within schools; hence, dependency within the school clusters was accounted for by adding school as a random factor. The dependency between the repeated measures was accounted for by fitting a compound symmetry matrix to the residual matrices (i.e., equal correlations between the repeated measures, as an autoregressive matrix did not improve fit).…”
Section: Methodsmentioning
confidence: 99%